Telework Management in Public Administration:: between Instrumental and Substantive Rationalitiesr (Management and Connections Journal, 2025)
From the substantive approach of organizations, the research aims to analyze tensions between the substantive and instrumental rationalities in the management of the Public Administration’s teleworking program. A qualitative approach is adopted, applying a case study and collecting data through documents and semi-structured interviews, obtaining results through content analysis. The results point to tensions in the organizational processes “hierarchy and norms”, “control” and “division of tasks”, such as the tension between the program objectives of ensuring a better quality of life for teleworkers and increasing organizational productivity, as well as the resulting from the formal normative provision for the participation of civil servant representatives in management without actually occurring in administrative practice. As a contribution of the study, ensuring applicability to the research results, possibilities for adjustmentsto the management of teleworking program in public organization are indicated.
Keywords: remote work; public management; rationality; public prosecutor's office